If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(3x + -5) = 19(7 + -1x) Reorder the terms: -6(-5 + 3x) = 19(7 + -1x) (-5 * -6 + 3x * -6) = 19(7 + -1x) (30 + -18x) = 19(7 + -1x) 30 + -18x = (7 * 19 + -1x * 19) 30 + -18x = (133 + -19x) Solving 30 + -18x = 133 + -19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '19x' to each side of the equation. 30 + -18x + 19x = 133 + -19x + 19x Combine like terms: -18x + 19x = 1x 30 + 1x = 133 + -19x + 19x Combine like terms: -19x + 19x = 0 30 + 1x = 133 + 0 30 + 1x = 133 Add '-30' to each side of the equation. 30 + -30 + 1x = 133 + -30 Combine like terms: 30 + -30 = 0 0 + 1x = 133 + -30 1x = 133 + -30 Combine like terms: 133 + -30 = 103 1x = 103 Divide each side by '1'. x = 103 Simplifying x = 103
| -6m+3=10-5m | | -2(3x+5)+4(2x+2)= | | 2x^3-10x^2-100x=72 | | 4y-4+y+24=6y-20-4y | | -17=-31-7f | | (268*366)/(4400*156) | | 3-(2x+5)=5+x+2(4-6) | | -104/-8x | | x-9=5x+15 | | (8+4q)(-9)= | | (4x-6)=90and(2x) | | 30-2x+6x+22=90 | | 5-3x=-11+x | | -x+38=2x+17 | | 8(x+4)+10=10x-2(x-5) | | 7.84cm= | | 7.84= | | -2x+14=x+2 | | x^2+7x+36.75=0 | | 3x-2=20-x | | 4-2c=8 | | -5x-29=145 | | (4x+3)*(3x+2)=0 | | x+6x-1=90 | | (4x-3)*(3x-2)=0 | | 3(2q+3)=5(2q+1) | | -log(x)=20 | | 4x^2+3x+12=12 | | 3(5c-1)-2=13c+13 | | 5x/6-2=3 | | -3x+23=x+3 | | 60x+70y=4200 |